Get into gear, Stilton! - Dami, Elisabetta, (Scholastic Inc., 2013)
Selected by the mayor to give a special driving demonstration, Geronimo Stilton realizes his driver's license has expired and he must do everything he can to pass the test again, learn about a new robot car, and catch a thief.